A Stable Photoluminescence of Waste Derived Acrylic Plastics (PMMA) and MAPbBr 3 Composite Film. Issue 1 (June 2021) - Mahen, E C S; Nuryadin, B W; Permatasari, F A; Aimon, A H; Suprijadi; Iskandar, F
Abstract: This paper reports the synthesis and characterization of a composite thin of waste-derived acrylic plastic (PMMA) and MAPbBr 3 perovskite nanocrystal that prepared by ligand assisted re-precipitation (LARP) method. The composite thin film prepared from MABr, PbBr2, oleic acid and oleyl amine, N, N-dimethylformamide (DMF) as a precursor, toluene as a solvent, and waste-derived PMMA as polymer, and then deposited on glass substrate using a spin coater with different speed. As a result, the highest transmittance value was around 90% for the sample with a high spin speed (3000 rpm). The photoluminescence of MAPbBr3 film, when illuminated by UV shows a bright green color with a peak at 536 nm wavelength and maximum luminescence found in the sample with the lower spin speed (1000 rpm). Thus, the fabricated perovskite composite thin film using recycled acrylic plastic has a good prospect to be applied in optoelectronic application.